INFORMATION COMMUNICATION TECHNOLOGY FOR PROFESSIONAL DEVELOPMENT OF ADULT EDUCATION STAFF MANAGEMENT: CHALLENGES AND PROSPECTS IN THE SILESIA REGION - Ochoa Siguencia, Luis; Marzano, Gilberto; Herman, Damian (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This research focuses on the professional development of Adult Education Staff through the implementation of Information and Communication Technology skills. We present the data from a desk  and field research carried out in the Silesia Region - Poland, on a sample formed of Adult educators working in different Non - formal Education Institutions. The research tool used in our paper is an online questionnaire developed withing the ERASMUS+ project “Upskillead – 2016-1-SI01-KA204-021588” KA2 - Strategic Partnership in the field of Adult Education. The final research objective is to find solutions useful to develop digital competence of adult people through in-house training's, seminars and informal learning applications. Moreover, this paper illustrates benefits, limitations, challenges in using digital resources and tools in adult education.